Pantheism in the Studies on Nature of Johann Wolfgang von Goethe - Rojas Alvarado, Arturo (2025)
This article studies the philosophical thought of Johann Wolfgang von Goethe, inside his ontological conception from his pantheism and his studies of nature, identifying the elements where both are related.